Noncoding rules of survival: epigenetic regulation of normal and malignant hematopoiesis - Wallace, LaShanale; Obeng, Esther A. (Frontiers in Molecular Biosciences, 2023)
Hematopoiesis is an essential process for organismal development and homeostasis. Epigenetic regulation of gene expression is critical for stem cell self-renewal and differentiation in normal hematopoiesis. Increasing evidence shows that disrupting the balance between self-renewal and cell fate decisions can give rise to hematological diseases such as bone marrow failure and leukemia. Consequently, next-generation sequencing studies have identified various aberrations in histone modifications, DNA methylation, RNA splicing, and RNA modifications in hematologic diseases. Favorable outcomes after targeting epigenetic regulators during disease states have further emphasized their importance in hematological malignancy. However, these targeted therapies are only effective in some patients, suggesting that further research is needed to decipher the complexity of epigenetic regulation during hematopoiesis. In this review, an update on the impact of the epigenome on normal hematopoiesis, disease initiation and progression, and current therapeutic advancements will be discussed.